Anisotropic nitriding behavior upon formation of expanded hcp in Co-Cr alloys. (October 2021) - Akhlaghi, Maryam; Martin, Stefan; Dallmann, Johannes; Hock, Rainer; Körner, Carolin; Leineweber, Andreas
Abstract: The transformation from hexagonal close packed (hcp) to face-centered cubic (fcc) crystal structure upon gaseous nitriding of Co-Cr alloy with initial hcp crystal structure was investigated. During early stages of low-temperature nitriding at 400°C, new reflections on the low-angle side of the hcp-substrate reflections in X-ray diffraction patterns can be attributed to the formation of hcp phase with an expanded lattice on the surface. Prolonged nitriding treatment and nitriding at higher temperatures result in transformation of this expanded hcp into an expanded fcc. An anisotropic progress of mentioned transformation on differently-oriented hcp crystallites is observed. The transformation is slower in hcp orientations with the highest Schmid factor of the basal slip mode with respect to the nitriding direction. This is discussed in a view of developed macrostress in early stages of nitriding and its influence on plastic anisotropic deformation of hcp variants. Graphical abstract: Image, graphical abstract